Literary Aftershocks of the Revolution: Recent Developments in Algerian Literature - Eric Sellin (Studies in 20th & 21st Century Literature, 1980)
Most Algerian Francophone literature has been written since 1950, and thus the development of that literature has been intimately linked to the political events which forged the Algerian nation. Especially influential was the 1954-62 war of independence which for many years was a major contextual element in the literature. With the passage of time, the Revolution has begun to be less and less cognitive in the lives and works of the young writers. For some, Revolution lives on in the oneiric evocations of horrors glimpsed, for others it is something relegated to history, whereas for yet others it has become a political and social device. The role the Revolution plays in a writer's creativity has tended to dichotomize the literature into a conservative branch of inward- and backward-looking patriotism and a radical branch of outward- and forward-looking experimentation. Both branches present equally fervent defenses of their loyalty to their country based on a variety of arguments, but the radical branch, regardless of its relative worth in terms of internal affairs, certainly is the branch which tends to transcend national idiom and to express itself in terms of wide-spread and universal literary values.
Keywords: Algerian literature; Algerian Francophone Literature; 1954-62 war of independence; the Revolution; politics; society; creativity; patriotism; experimentation